Faktor-Faktor yang Mempengaruhi Kinerja Usaha Pedagang Eceran Studi Kasus: Pedagang Kaki Lima Di Kota Yogyakarta - Endang Hariningsih; Rintar Agus Simatupang (Jurnal Riset Manajemen dan Bisnis, 2008)
The aim of th* stufu was to recognize the faaors it{luencing theperfonnances of raailers.rThosefactors were age, mwital status, mtmber of dependan*, level of efucation, working hours, irwentory level, location, ond number of employees. The performwtces of the venfurs were meoswed byusing margin profit. The data were obtained by doing suruey questionnaires completed by street vendors. Smtples were obtained through mahod probability sompling with simple rutdom sornpling teclmique. The data were, then, analyzed byusing multiple regression analysis. The result of this study illustrated that the age, the marital status, the numberof dependan*, the educational level, the working hours, the retailers *perience before being independent, their uperience undq c-urrent position, the stock level, and the location simultowously as awhole, had significant andpositive irfluence on the mogin prafit. Hawever; partialb the individual variables that influenced the mwgin profit of the vendors were the age, the marital status, the iwentory level, and the number of employees.Keywords : Informal s ector, street vmdors, p*formances.